The role of the common tasks of professional activity in the organization of the educational process baccalaureate. (Journal of Educational Sciences, 2016)
We consider modeling of typical problems of the future professional BS in Physics at the example of teaching special subjects. Notes the role of typical problems professional bachelor to master the educational competence. The basic components of the modeling common tasks professional bachelor in teaching special subjects. Describes the relationship model components forming the professional orientation of teaching special subjects. Bachelor celebrated innovation in the context of the quality of modern specialist.
Keywords: activity; process; competence; common tasks; component; professional activities; educational process; special disciplines